2012
DOI: 10.1246/cl.2012.159
|View full text |Cite
|
Sign up to set email alerts
|

Small- and Large-angle X-ray Scattering Studies of Nanometer-order Sulfuric Acid Solution in Carbon Micropores

Abstract: The structure of nanometer-order sulfuric acid solution in carbon micropores is investigated by large-and small-angle X-ray scattering experiments. The electron radial distribution function of the nanosolution is different from that of bulk solution. The intermolecular structure of nanosolution does not change with fractional filling. These results and the dependency of density fluctuations of the system with fractional filling showed that the nanometer-order sulfuric acid solutions in carbon micropores form a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…We reported that a benzylammonium (BA)-modified (Scheme b) smectite was found to be the most effective adsorbent for the caffeine adsorption in aqueous solution among commercially available organoclays containing organoammonium ions as quaternary long-chain alkylammonium and BA . Transmission XRD with an angle-dispersion diffractometer , and small-angle X-ray scattering have been recently adopted to investigate the interlayer expansion of organically functionalized smectites in water , and in aqueous solutions of caffeine . BA-exchanged smectites swelled in liquid water by ∼0.2 nm and expanded further by 0.1 nm in an aqueous caffeine solution.…”
Section: Introductionmentioning
confidence: 99%
“…We reported that a benzylammonium (BA)-modified (Scheme b) smectite was found to be the most effective adsorbent for the caffeine adsorption in aqueous solution among commercially available organoclays containing organoammonium ions as quaternary long-chain alkylammonium and BA . Transmission XRD with an angle-dispersion diffractometer , and small-angle X-ray scattering have been recently adopted to investigate the interlayer expansion of organically functionalized smectites in water , and in aqueous solutions of caffeine . BA-exchanged smectites swelled in liquid water by ∼0.2 nm and expanded further by 0.1 nm in an aqueous caffeine solution.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we have paid attention to organic cations containing aromatic ring for using organically modified smectites (a natural montmorillonite and synthetic saponite) through cation-exchange reactions with BA and neostigmine (CONH, which has been reported for effective adsorption of phenylphenol; Scheme e). Transmission X-ray diffraction (XRD) using an angle-dispersion diffractometer was used for pursuing the nanostructural change in the aromatic ammonium–smectites upon the adsorption in aqueous media. We will discuss a role of the nanostructures, which correlate the adsorption behavior of caffeine.…”
Section: Introductionmentioning
confidence: 99%
“…Microscopic measurement methods such as X-ray diffraction (XRD) 1 and extended X-ray absorption fine structure (EXAFS) 2 enable the study of the behavior of adsorbed molecules. New porous materials such as metalorganic frameworks (MOFs) 3 and porous organosilicates 4 have designable nanostructures.…”
mentioning
confidence: 99%